The vacation rental : a novel - Sise, Katie (Little A, 2024)
"When Georgia rents her country home for the month of August, it's off to the relaxing Connecticut shore for her; her husband, Tom; and their young daughter. It's just what they need to ease family tensions and reconnect. All that's left to do is leave behind their house keys--to a stranger. For Anna, Georgia and Tom's house in the cool woodlands is a dream break from the oppressive heat of a New York City summer--and from an increasingly ill-fated relationship with her lover. A month apart and Anna can clear her head and reassess her future. She's found the perfect place to do it. As the weeks wear on, Georgia and Anna discover that the pleasures of escape are as difficult to trust in as the comforts of home. And neither one can shake the feeling that something is about to go terribly wrong." -- Amazon.com